A lipidomics study reveals hepatic lipid signatures associating with deficiency of the LDL receptor in a rat model - Hong Yu Wang; Chao Quan; Chunxiu Hu; Bingxian Xie; Yinan Du; Liang Chen; Wei Yang; Liu Yang; Qiaoli Chen; Bin Shen; Bian Hu; Zhihong Zheng; et al. (Biology Open, 2016)
The low-density lipoprotein receptor (LDLR) plays a critical role in the liver for the clearance of plasma low-density lipoprotein (LDL). Its deficiency causes hypercholesterolemia in many models. To facilitate the usage of rats as animal models for the discovery of cholesterol-lowering drugs, we took a genetic approach to delete the LDLR in rats aiming to increase plasma LDL cholesterol (LDL-C). An LDLR knockout rat was generated via zinc-finger nuclease technology, which harbors a 19-basepair deletion in the seventh exon of the ldlr gene. As expected, deletion of the LDLR elevated total cholesterol and total triglyceride in the plasma, and caused a tenfold increase of plasma LDL-C and a fourfold increase of plasma very low-density lipoprotein (VLDL-C). A lipidomics analysis revealed that deletion of the LDLR affected hepatic lipid metabolism, particularly lysophosphatidylcholines, free fatty acids and sphingolipids in the liver. Cholesterol ester (CE) 20:4 also displayed a significant increase in the LDLR knockout rats. Taken together, the LDLR knockout rat offers a new model of hypercholesterolemia, and the lipidomics analysis reveals hepatic lipid signatures associating with deficiency of the LDL receptor.